2021
DOI: 10.1002/ajmg.a.62118
|View full text |Cite
|
Sign up to set email alerts
|

Alazami syndrome: Report of three Indian patients with phenotypic spectrum from adolescence to adulthood

Abstract: Alazami syndrome (ALAZS) (MIM 615071) is a rare autosomal recessive disorder characterized by short stature, dysmorphic facial features, developmental delay, and impaired intellect. It was first reported in a Saudi Arabian family in 2012. Three Indian patients affected with ALAZS, one boy aged 13 years and other two sisters in their 40s are presented. These patients had few unreported dysmorphic facial features: high arched eyebrows and dental overcrowding. No microcephaly was noted in the sisters. One of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Initially, Hollink et al (2016) reported on two patients with normal birth growth parameters but developed failure to thrive at a later age. Thereafter, the description of these similar characteristics was reported in other studies (Bajafar et al, 2019; Das et al, 2021; Gana et al, 2020; Hollink et al, 2016; Ivanovski et al, 2020; Wojcik et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Initially, Hollink et al (2016) reported on two patients with normal birth growth parameters but developed failure to thrive at a later age. Thereafter, the description of these similar characteristics was reported in other studies (Bajafar et al, 2019; Das et al, 2021; Gana et al, 2020; Hollink et al, 2016; Ivanovski et al, 2020; Wojcik et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, congenital structural anomalies are anticipated in AS; yet, they are known to be under‐reported. Previous structural anomalies reported in Alazami patients include cleft palate (Das et al, 2021; Hollink et al, 2016), atrial septal defect (Imbert‐Bouteille et al, 2019), genito‐renal anomaly (Das et al, 2021; Dateki et al, 2018), and ocular anomaly (Das et al, 2021; Imbert‐Bouteille et al, 2019). The findings in our cohort emphasize the importance of screening for structural anomalies as (4/12) patients had atrial septal defect, (6/12) patients had genito‐renal anomaly, and (7/12) patients have an ocular anomaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysmorphic features include a triangular face with malar hypoplasia, deep-set eyes with narrow palpebral fissures, sparse eyebrows, wide nasal bridge, short philtrum, full lips and widely spaced teeth [ 10 ]. Occasionally, some common features such as low-set ears, prominent forehead, high palate and micrognathia are described [ 10 , 11 ]. In most cases disproportionate mild microcephaly compared with severe short stature is observed, too [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases disproportionate mild microcephaly compared with severe short stature is observed, too [ 10 ]. Additionally, congenital heart defects and hypospadias have been reported [ 5 , 11 ]. Patients may present with a variety of behavioural disorders, such as excessive agitation, aggressiveness, self-stimulation and autistic features.…”
Section: Introductionmentioning
confidence: 99%